Differences in Learning Indonesian Literature in the 2013 Curriculum and the Independence Curriculum in Junior High Schools in Indonesia - Wardani, Nugraheni Eko; Suwandi, Sarwiji; Ulya, Chafit; Setiyoningsih, Titi (KnE Social Sciences, 2023)
Before the Covid-19 pandemic, Indonesia had been implementing the 2013 curriculum for primary and secondary schools. However, in response to the pandemic’s impact, Indonesia later shifted to an independent curriculum for primary and secondary schools. This study aims to elucidate the differences in learning Indonesian literature between the 2013 curriculum and the independent curriculum in Indonesian Junior High Schools. The research adopts a qualitative descriptive approach, employing data collection techniques such as document analysis and interviews with informants. Method triangulation is used to ensure data validity. Data analysis comprises data reduction, data analysis, and data presentation. The findings of the study reveal that under the 2013 curriculum, learning Indonesian literature was structured through a learning implementation plan (RPP). This plan encompassed core competencies, basic competencies, competency achievement indicators, learning objectives, approaches, models, and learning methods, as well as learning media, resources, steps, and assessment methods. On the other hand, the independent curriculum utilized a learning module, incorporating learning outcomes, learning objectives, approaches, models, and learning methods, as well as learning media, resources, student profiles of Pancasila (Indonesia’s national ideology), learning steps, and assessment methods. Notably, in the context of the independent curriculum, teachers are required to conduct diagnostic assessments and employ differentiated learning strategies to cater to individual student needs. Keywords: differences in learning Indonesian literature, 2013 curriculum, independence curriculum